Social media in the adult population: Potential outcomes and its relationship with self-esteem and well-being - A systematic literature review - Giorgia Rossi; Caterina Fiorilli; Giacomo Angelini; Teresa Grimaldi Capitello (Computers in Human Behavior Reports)
The rapid expansion of social media and digital device use has created a new phenomenon: Problematic Internet Use (PIU). Numerous studies have explored the potential impact of digital use on the self-esteem and well-being of users. This systematic review examines and synthesizes the findings of studies that have investigated the possible outcomes of self-esteem, anxiety, depression, and loneliness. A search on PsycINFO, PubMed, and Scopus identified 37 eligible studies that investigated these variables in a sample of adults (18 years and above). The findings from these studies were categorized based on their impact on self-esteem, anxiety, depression, and loneliness. They reported the relationship of these variables with other interesting factors such as Fear of Missing out (FoMo), social anxiety, emotional investment, and differences between young adults and older adults and the differences based on gender. However, the studies included in the review have limitations, such as small sample sizes, cross-sectional design, and self-reporting to evaluate the possible consequences. To gain a deeper understanding of the mechanisms underlying the relationship between digital use and its impact on users, future studies must investigate this relationship through qualitative and longitudinal studies.